County-Level Associations Between Pregnancy-Related Mortality Ratios and Contextual Sociospatial Indicators. Issue 5 (5th May 2022) - Barrera, Chloe M.; Kramer, Michael R.; Merkt, Peter T.; Petersen, Emily E.; Brantley, Mary D.; Eckhaus, Lindsay; Beauregard, Jennifer L.; Goodman, David A.
Abstract : This retrospective population-based study of pregnancy-related deaths found county-level sociospatial indicators to be associated with pregnancy-related mortality ratios overall and by race and ethnicity. Abstract : OBJECTIVE: To characterize county-level differences in pregnancy-related mortality as a function of sociospatial indicators. METHODS: We conducted a cross-sectional multilevel analysis of all pregnancy-related deaths and all live births with available ZIP code or county data in the Pregnancy Mortality Surveillance System during 2011–2016 for non-Hispanic Black, Hispanic (all races), and non-Hispanic White women aged 15–44 years. The exposures included 31 conceptually-grounded, county-specific sociospatial indicators that were collected from publicly available data sources and categorized into domains of demographic; general, reproductive, and behavioral health; social capital and support; and socioeconomic contexts. We calculated the absolute difference of county-level pregnancy-related mortality ratios (deaths per 100, 000 live births) per 1-unit increase in the median absolute difference between women living in counties with higher compared with lower levels of each sociospatial indicator overall and stratified by race and ethnicity. RESULTS: Pregnancy-related mortality varied across counties and by race and ethnicity. Many sociospatial indicators were associated with county-specific pregnancy-related mortality ratios independent of maternal age, population size, and Census region. Across domains, the most harmful indicators were percentage of low-birth-weight births (absolute ratio difference [RD] 6.44; 95% CI 5.36–7.51), percentage of unemployed adults (RD 4.98; 95% CI 3.91–6.05), and food insecurity (RD 4.92; 95% CI 4.14–5.70). The most protective indicators were higher median household income (RD −2.76; 95% CI −3.28 to −2.24), percentage of college-educated adults (RD −2.28; 95% CI −2.81 to −1.75), and percentage of owner-occupied households (RD −1.66; 95% CI −2.29 to −1.03). The magnitude of these associations varied by race and ethnicity. CONCLUSION: This analysis identified sociospatial indicators of pregnancy-related mortality and showed an association between pregnancy-related deaths and place of residence overall and stratified by race and ethnicity. Understanding county-level context associated with pregnancy-related mortality may be an important step towards building public health evidence to inform action to reduce pregnancy-related mortality at local levels.